The Influence of Romania’s Banking Institutions in the Absorption of Structural and Cohesion Funds in the Period 2014-2020 - Dumitru BELDIMAN; Mihai Octavian PERPELEA (Revista de Management Comparat International)
The absorption of EU funds made available to each member state of the European Union is one of their main priorities, also a priority of Romania in the 2014-2020 programming period, given that European funds are considered an important alternative source for financing the economy, with the help of which we will be able to meet the three new priorities of Europe Strategy 2020, namely “smart growth, sustainable growth, growth favorable for inclusion”. In our opinion, the authors, one of the most important obstacles in the absorption of European funds, obstacle that is common to all Member States, is the inability of potential applicants for EU funds, be they representatives of local public authorities, NGOs, religious units, SMEs, micro enterprises, other categories of eligible applicants, etc. to demonstrate the financial sustainability of the project during implementation, namely to be able to sustain the imposed compulsory co-financing programs as a share of total eligible costs of the project and bear the ineligible costs of the project. The demonstration of financial sustainability during the implementation of a project financed from European funds can be made by the applicant either by demonstrating its ability to self-finance the charges imposed by the managing authority of the funding program, namely through the co-financing share of eligible and ineligible expenses for the project, either through a credit agreement concluded with a bank or through a letter of guarantee, letter of comfort, etc. issued by a banking institution. In this regard, as it can be seen, the role of banking institutions in the absorption of European funds is particularly important, aspect that shall be highlighted in this article, which is oriented towards the discovery of hypotheses not towards the confirmation or refutation of hypotheses.